SINARA Application to Detect Cervical Cancer Risk: Development and Validity - Madiuw, Devita; Nivaan, Goldy; Baumase, Riko (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
The coverage of cervical cancer screening in Indonesia is 6.83% and in Maluku is 7.02% which is still low, even though affordable IVA examinations are available at health centers. Not knowing the risk of cervical cancer is one of the obstacles to low awareness of cervical cancer screening. Previous research has developed a valid and reliable SINARA instrument to detect cervical cancer risk. This study aims to develop and test the validity of the SINARA application, a smartphone application for detecting cervical cancer risk. This quantitative study uses the PDCA (Plan, Do, Check, Action) approach. The study was conducted from July to September. The research sample was 30 women of childbearing age in Ambon City, with a purposive sampling technique. Data collection was carried out offline using questionnaires and online using Google Forms. This study produced the SINARA application with validity test results> 0.361 and a Cronbach alpha value of 0.935, and good quality through usability test results of 82.82%. A high-quality SINARA application is expected to help increase the participation of women in carrying out cervical cancer screening at health facilities. It is recommended to integrate this with the health office to identify women at risk of cervical cancer.